The Organic Photocatalyst for Hydrogen Production under the Ambience of Ultraviolet Light - NMDwidiani; NPG Suardana; Willy Satrio Nugroho; IGN Nitya Santhiarsa; IGK Puja, WN Septiadi; IGK Puja, WN Septiadi; AA Adhi Suryawan; ING Wardana (Journal of Applied Science and Engineering)
Hydrogen production by photocatalysis has a potential to be fully green green hydrogen production process. However, metal photocatalyst require costly noble metal to performing well. Several organic photocatalysts have been made but not every organic photocatalysts synthesized with fully green process. This study provides biomassa based organic catalyst from rice Husk Ash (RHA) synthesized using enzymatic organic acid from Pineapple Peel juice. The immersion on Bromelain containing pineapple Peel juice divides the RHA into sunked Carbon nanomaterials (SCNM) and floating CNM (FCNM). The photocatalytic hydrogen production, photocurrent test, UV-Vis spectroscopy, FTIR, and SEM, and EDX characterization were performed. The results reveal the CuO and Si content determine the physical and Chemical properties of each CNM. FCNM has the best photocatalytic activity due to the spread CuO and Si content while SCNM is more concentrated. The FCNM produces 1132.1391 MoL.L^−1 H₂ , SCNM 754.5295Mol.L^−1 H₂, RHA 377.8021 Mol.L^−1 H₂, and Without CNM 188.4670 Mol.L−1 H2. Therefore, the photocatalytic activity of CNM depends on the distribution of photoactive content such as CuO and Si.